2006
DOI: 10.1152/ajprenal.00080.2006
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in heat shock protein 72 expression and localization in rats following renal ischemia-reperfusion injury

Abstract: Fekete, Andrea, Á dám Vannay, Á gota Vér, Krisztina Rusai, Veronika Mü ller, György Reusz, Tivadar Tulassay, and Attila J. Szabó. Sex differences in heat shock protein 72 expression and localization in rats following renal ischemia-reperfusion injury. Am J Physiol Renal Physiol 291: F806 -F811, 2006. First published April 11, 2006 doi:10.1152/ajprenal.00080.2006.-Previously, we demonstrated gender differences in Na-K-ATPase (NKA) expression and function after renal ischemia-reperfusion (I/R) injury (Sex diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
44
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 25 publications
4
44
0
Order By: Relevance
“…Several factors were found to be associated with sex differences in ischemia/reperfusion-induced acute kidney injury: mRNA expression of endothelin-1, a causal factor for ischemic acute kidney injury, is increased at an early phase following reperfusion in male rats, but not in female rats (4); enzyme activity of Na + ,K + -ATPase after ischemia/reperfusion treatment is higher in female than in male rats (5); heat shock protein 72 exhibits higher basal and post-ischemic levels in the kidney of female rats (6); endothelial nitric oxide synthase protein is increased in females relative to males, reduced by oophorectomy, and increased by estradiol treatment (7); ischemia induced superoxide dismutase activity is attenuated and reactive oxygen species are increased in intact males, but not in orchidectomized males, and these parameters returned to normal levels with dihydrotestosterone administration (8); renal venous plasma norepinephrine levels after reperfusion are markedly elevated in male rats, but not in female rats (9). In addition, proteomic analysis showed that the b subunit of F 1 F O -ATPase was significantly up-regulated 2 h after the reperfusion in ischemia/reperfusion-treated male rat kidneys, but not in female kidneys (10).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors were found to be associated with sex differences in ischemia/reperfusion-induced acute kidney injury: mRNA expression of endothelin-1, a causal factor for ischemic acute kidney injury, is increased at an early phase following reperfusion in male rats, but not in female rats (4); enzyme activity of Na + ,K + -ATPase after ischemia/reperfusion treatment is higher in female than in male rats (5); heat shock protein 72 exhibits higher basal and post-ischemic levels in the kidney of female rats (6); endothelial nitric oxide synthase protein is increased in females relative to males, reduced by oophorectomy, and increased by estradiol treatment (7); ischemia induced superoxide dismutase activity is attenuated and reactive oxygen species are increased in intact males, but not in orchidectomized males, and these parameters returned to normal levels with dihydrotestosterone administration (8); renal venous plasma norepinephrine levels after reperfusion are markedly elevated in male rats, but not in female rats (9). In addition, proteomic analysis showed that the b subunit of F 1 F O -ATPase was significantly up-regulated 2 h after the reperfusion in ischemia/reperfusion-treated male rat kidneys, but not in female kidneys (10).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen also affects the mitogen-activated protein kinases (MAPK) produced after renal I/R injury, via increasing the activation of extracellular signal-related kinase (ERK) that promotes cell survival, and decreasing the activation of p38 that promotes cell death (Park et al 2004). Estrogen also increases the expression of heat-shock protein HSP-72 in the renal tubular cells which, in turn, mediates Na + /K + ATPase and is essential for maintenance of actin cytoskeletal integrity; thus preventing the time-dependent translocation of Na + /K + ATPase from the basolateral to the apical membranes of the proximal tubular cells following renal I/R injury (Fekete et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] There are consistent findings that females are more resistant to I/R-induced renal injury than males. A few factors were found to be associated with sex differences in I/R-induced ARF of rodent models: mRNA expression of endothelin-1, a causal factor for ischemic ARF, 9) is increased at an early phase following reperfusion in male rats, but not in female rats; 4) enzyme activity of Na ϩ , K ϩ -ATPase after I/R treatment is higher in female than in male rats 7) ; heat shock protein (Hsp) 72 exhibits the higher basal and postischemic levels in the kidney of female rats.…”
mentioning
confidence: 91%
“…A few factors were found to be associated with sex differences in I/R-induced ARF of rodent models: mRNA expression of endothelin-1, a causal factor for ischemic ARF, 9) is increased at an early phase following reperfusion in male rats, but not in female rats; 4) enzyme activity of Na ϩ , K ϩ -ATPase after I/R treatment is higher in female than in male rats 7) ; heat shock protein (Hsp) 72 exhibits the higher basal and postischemic levels in the kidney of female rats. 8) Investigation of sex differences at the molecular levels might therefore provide a new area for mechanistic study of ischemic ARF.…”
mentioning
confidence: 99%